The victory of the cross : salvation in Eastern Orthodoxy - Payton, James R., 1947- (Downers Grove, IL : : IVP Academic, 2019)
"How can Christians claim that the death of Jesus Christ on the cross is a victory? Yet the doctrine of salvation affirms precisely that: in his death and his resurrection, Christ is victorious over the power of sin and death. The articulation of this tenet of faith has taken different shapes throughout the church's life and history. Eastern Orthodoxy has made its own contributions to the belief in salvation through Christ, but its expressions sometimes sound unfamiliar to Western branches of the church. Here James Payton, a Western Christian with a sympathetic ear for Eastern Orthodoxy, explores the Orthodox doctrine of salvation. Payton helps Christians of all traditions listen to Orthodox brothers and sisters so that together we might rejoice, 'Where, O death, is your victory?'"--Publisher statement.
Preliminary note on Orthodox terminology and liturgies -- Introduction -- Setting the stage : viewing the cross -- The need for salvation -- The focus of the savior -- The economy of salvation : how God saved humanity -- Deification : the God of salvation -- Becoming like God : the path of salvation -- The sign of the cross -- Appendix. On Orthodox usage of biblical terms for the reception of salvation.
Includes bibliographical references (pages 191-194) and indexes.
Keywords: Orthodox Eastern Church -- Doctrines; Orthodox Eastern Church..; Salvation -- Christianity -- History of doctrines; Salvation -- Orthodox Eastern Church; Salvation -- Christianity -- History of doctrines..; Theology, Doctrinal..